Legal Analysis of the Criminalization of Perpetrators of Criminal Acts of Carrying Sharp Weapons and Criminal Acts of Assault (Case Study of Criminal Case Number: 599.Pid..B/2024/PN Jkt Pst) - Rizal, Syaifur; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The crime of assault is one form of violation of the law that often occurs in society. Cases of assault often have serious impacts, both physically and psychologically for the victim. There are tools that help assault, although these tools are actually made for good purposes but can be misused in committing crimes. Many cases that are tried involve defendants who carry sharp weapons without permission, such as daggers, sickles, samurai, and machetes. The increase in these cases shows the need for further research to understand the factors that encourage individuals, including adolescents, to carry and use sharp weapons. The aproach method used is normative juridical, namely a library legal research conducted by examining library materials or secondary data only using deductive thinking methods. The writing specifications use descriptive analysis, the sources and types of data used are primary and secondary data. The data collection method is by collecting data using secondary data collection methods. The problem is analyzed with the theory of criminal responsibility, the theory of Pancasila justice and Islamic justice. The judge's consideration in issuing Decision Number 599/Pid.B/2024/PN Jkt Pst, which assessed that the defendant was proven to have committed the crime of carrying a sharp weapon without a permit and serious assault is a decision that reflects the aplication of the theory of legal certainty through a comprehensive analysis of facts, evidence, and relevant legal aspects, so as to provide legal certainty and protection of rights for all parties. The Criminalization Process for the Crime of Carrying Sharp Weapons and the Crime of Serious Assault in the Case of Decision Number: 599/Pid.B/2024/Pn Jkt Pst. is a legal mechanism to uphold justice by considering material and formal aspects, and prioritizing retributive and preventive functions. Through the analysis of Decision Number 599/Pid.B/2024/PN Jkt Pst, where the defendant was found guilty of possessing a sharp weapon without a permit and serious assault, this thesis shows how the aplication of criminalization provides legal certainty while protecting the interests of the community and victims. Criminalization is not only a form of punishment, but also an effort at rehabilitation and prevention in order to maintain social order.